Sleep improvement with levodopa/carbidopa intestinal gel infusion in Parkinson disease. (11th January 2013) - Zibetti, M.; Rizzone, M.; Merola, A.; Angrisano, S.; Rizzi, L.; Montanaro, E.; Cicolin, A.; Lopiano, L.
<x xml:space="preserve">Abstract</x> Background Sleep disorders are common in patients with advanced Parkinson's disease (PD). Nocturnal akinesia and sleep fragmentation frequently coexist with daytime sleepiness, influencing daytime functioning. Levodopa/carbidopa intestinal gel (LCIG) infusion has been shown to improve motor complications in advanced PD, and preliminary findings suggest that sleep might improve following LCIG infusion. Objective To analyze the impact of LCIG infusion on sleep symptoms and daytime sleepiness in patients with PD. Methods Twelve consecutive patients with PD completed the PD‐Sleep‐Scale‐version‐2 (PDSS‐2) and the Epworth‐Sleepiness‐Scale (ESS) at baseline and after 2–4 months of LCIG treatment. Activities of daily living, motor symptoms and complications were assessed with the Unified‐PD‐rating‐Scale section II, III, and IV. Results Nocturnal sleep improved substantially in all patients switched to LCIG infusion. PDSS‐2 total score and subscores for 'Disturbed sleep', 'Motor symptoms at night', and 'PD symptoms at night' were significantly reduced. ESS measures of daytime sleepiness also improved. Motor complications and activities of daily living improved significantly with LCIG. Conclusion Subjective measures of sleep quality and daytime sleepiness improve in patients with advanced PD undergoing LCIG infusion. Further studies with a larger number of patients and polysomnographic recordings are needed to confirm the beneficial effect on sleep and clarify the underlying mechanisms.